Heart of venom - Estep, Jennifer (New York, N.Y. : Pocket Books, 2013)
Gin Blanco is out for blood when a fire elemental and his goons kidnap her close friend Sophia Deveraux.
Contains excerpt from The Spider.
Keywords: Assassins -- Fiction; Magic -- Fiction; Paranormal fiction